Overexpression of squamous cell carcinoma antigen in idiopathic pulmonary fibrosis: clinicopathological correlations. Issue 9 (14th March 2008) - Calabrese, F; Lunardi, F; Giacometti, C; Marulli, G; Gnoato, M; Pontisso, P; Saetta, M; Valente, M; Rea, F; Perissinotto, E; Agostini, C
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is a chronic progressive disorder with a poor prognosis. Epithelial instability is a crucial step in the development and progression of the disease, including neoplastic transformation. Few tissue markers for epithelial instability have been reported in IPF. Squamous cell carcinoma antigen (SCCA) is a serine protease inhibitor typically expressed by dysplastic and neoplastic cells of epithelial origin, more often in squamous cell tumours. At present, no information is available on its expression in IPF. Methods: SCCA and transforming growth factor β (TGFβ) expression in surgical lung biopsies from 22 patients with IPF and 20 control cases was examined. An in vitro study using A549 pneumocytes was also conducted to investigate the relationship between SCCA and TGFβ expression. SCCA and TGFβ epithelial expression was evaluated by immunohistochemistry and reverse transcription–PCR (RT-PCR). SCCA values were correlated with different pathological and clinical parameters. Time course analysis of TGFβ expression in A549 pneumocytes incubated with different SCCA concentrations was assessed by real time RT–PCR. Results: SCCA was expressed in many metaplastic alveolar epithelial cells in all IPF cases with a mean value of 24.9% while it was seen in only two control patients in up to 5% of metaplastic cells. In patients with IPF, SCCA correlated positively with extension of fibroblastic foci (r = 0.49, p = 0.02), expression of TGFβ (r = 0.78, p<0.0001) and with carbon monoxide transfer factor decline after 9 months of follow-up (r = 0.59, p = 0.01). In vitro experiments showed that incubation of cultured cells with SCCA induced TGFβ expression, with a peak at 24 h. Conclusion: Our findings provide for the first time a potential mechanism by which SCCA secreted from metaplastic epithelial cells may exert a profibrotic effect in IPF. SCCA could be an important biomarker in this incurable disease.